Atención al Cliente de la empresa Comercial Torres del cantón Babahoyo provincia de los Ríos, del periodo 2023. - Vite Mindiola, María Del Carmen (2025)
The case study "Customer Service at Comercial Torres" analyzes the main issues affecting the shopping experience at this establishment in Babahoyo canton during the 2023 period. The company faces challenges such as a lack of accessibility for people with mobility impairments, insufficient staff availability during peak hours, the absence of a clear process for product returns and exchanges, inconsistent application of customer service policies, and the lack of an adequate rest area for customers. These factors negatively impact consumer satisfaction and the business's competitiveness. To address these shortcomings, the research is based on surveys and interviews with customers and employees, aiming to assess service quality and propose improvement strategies. Suggested measures include adapting facilities for accessibility, hiring additional staff during high-demand hours, standardizing the returns process, and providing ongoing staff training. Through these actions, the study seeks to optimize customer service, enhance loyalty, and strengthen Comercial Torres' image in the local market.